Critical numbers of attractive Bose-Einstein condensed atoms in asymmetric traps - Gammal, A.; Tomio, Lauro [UNESP]; Frederico, T. (American Physical Society (APS), 2002)
A quantitative analysis of the critical number of attractive Bose-Einstein condensed atoms in asymmetric traps was studied. The Gross-Pitaevskii (GP) formalism for an atomic system with arbitrary nonspherically symmetric harmonic trap was also discussed. Characteristic limits were obtained for reductions from three to two and one dimensions from three to two and one dimensions, in perfect cylindrical symmetries as well as in deformed ones.
Keywords: Approximation theory; Condensation; Ground state; Scattering; Bose Einstein condensation (BEC); Quantum theory